Effect of a biological response modifier on cellular death mechanisms at drying off - Dallard, Bibiana Elisabet (2008)
Agents that increase natural protective mechanisms have been proposed for prevention and treatment of intramammary infections. The objective of this study was to describe the effects of a single intramammary infusion of a lipopolysaccharide (LPS)-based biological response modifier (BRM) on cellular death mechanism in uninfected and Staphylococcus aureus-infected bovine mammary glands during involution. Three groups of 12 cows, each one including 6 Staph. aureus-infected and 6 uninfected, were infused in two mammary quarters with BRM or placebo and slaughtered at 7, 14 and 21 d of involution. In infected quarters, BRM treatment produced a significant increase in percent of stained epithelial cells for the apoptosis-promoting protein Bax at every observation period. In addition, BRM produced a significant increase of immunostained stromal cells for Bax compared with placebo-treated quarters. BRM treatment produced an increase in percentages of epithelial cells staining with active caspase-3 at 7 d and 14 d of involution compared with placebo-treated quarters and a significant decrease in percentages of terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL)-positive epithelial cells at 7 d and 21 d of involution. In addition, BRM treatment caused an increase in percentage of stromal cells immunostaining for active caspase-3 and TUNEL. An increase of active caspase-3 and TUNEL epithelial and stromal cell immunostaining was observed in Staph. aureus-infected compared with uninfected quarters. Cellular proliferation, determined by Ki-67 immunostaining, was increased in epithelial and stromal cells from Staph. aureus-infected compared with uninfected quarters at every observation period. These results provide new insights into the mechanism of mammary cell death in uninfected and Staph. aureus-infected bovine mammary gland during involution and illustrate the effects of LPS-based BRM on apoptosis and cell proliferation during mammary involution.